Left Atrial Deformation Parameters Predict Left Atrial Appendage Function and Thrombus in Patients in Sinus Rhythm with Suspected Cardioembolic Stroke: A Speckle Tracking and Transesophageal Echocardiography Study - Karabay, Can Yücel; Zehir, Regayip; Güler, Ahmet; Oduncu, Vecih; Kalayci, Arzu; Aung, Soe Moe; Karagoz, Ali; Tanboga, Ibrahim Halil; Candan, Ozkan; Gecmen, Cetin; Erkol, Ayhan; Esen, Ali Metin; et al. (Echocardiography (Mount Kisco, N.Y.), 2013)
The aim of this study was to evaluate left atrial deformations using speckle tracking echocardiography for predicting left atrial appendage (LAA) thrombus in patients with suspected cardioembolic stroke who were in normal sinus rhythm. A total of 153 ischemic stroke patients (89 males, 64 females) in sinus rhythm who were suspected of having cardioembolism were included in the study. The patients underwent conventional two‐dimensional (2D) echocardiogram and 2D speckle tracking echocardiogram of the left atrium. Left atrial peak strain (LA‐4C‐RES) and left atrial precontraction strain (LA‐4C‐PUMP) were measured. Patients were divided into 2 groups according to the presence of thrombus in the LAA in transesophageal echocardiography. Both LA‐4C‐RES and LA‐4C‐PUMP values were found to be significantly lower in patients with LAA thrombus (11.8 ± 1.4% vs. 33 ± 12%, P < 0.001 and 5.8 ± 1.3% vs. 14.2 ± 5.3%, P < 0.001, respectively). A good inverse correlation was present between LA‐4C‐RES values and LAA morphologic parameters (with LAA area: r = −0.70, P < 0.001, with LAA length: r = −0.60, P < 0.001), and a good positive correlation was present with LAA emptying velocity with pulse Doppler (r = 0.74, P < 0.001). The area under the receiver‐operating characteristic curve of the LA‐4C‐RES was 0.94 (0.90–0.98, P < 0.001), for the LA‐4C‐PUMP, the area was 0.92 (0.87–0.96, P < 0.001) to predict LAA thrombus. Left atrial deformation parameters measured by 2D speckle tracking method was found to predict impaired LAA functions and the presence of LAA thrombus in ischemic stroke patients with suspected cardioembolism, but who are in sinus rhythm.